Authorship in Early Modern Jurisprudence: Paul Voet (1619-1667) on auctor and editor. - Varela, Laura Beck (Quaerendo, 2017)
Paul Voet (1619-1669), law professor at the University of Utrecht, opened his most famous work, published in 1657, with an unusual discussion of the five different types of auctores of juridical books (juris libri)--a precious source for the history of authorship in the jurisprudence and in the early modern respublica litteraria in general. This essay discusses the key concepts for his understanding of auctor and auctoritas in the field of jurisprudence, as well as the motivations for this uncommon inquiry into the notion of authorship. Besides his personal reasons (the rumors about the illegitimate authorship of some of his works), the detailed taxonomy of legal auctores also helped him to build a cogent argument against the validity of canon law in the United Provinces. His aim was to redesign the history of legal tradition and to dispute the authority of certain canon law sources, such as Gratian's Decretum.